The Concepts of Value and "Early and Rude society" in the Work of Adam Smith - Piqué, Pilar (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The work has two main objectives. First of all, to synthesize the recent debates in the historiography of economic thought about the notions of “value” and “early and rude society” in The Wealth of Nations. Secondly, to propose a reinterpretation of the role that Adam Smith assigns to these two notions. Two research hypotheses are expected to be demonstrated: 1) that most historians of economic thought interpreted that the Smithian example of how the law of value governs in an “early and rude society” did not make any contribution to the political economy because it cannot say anything about the concept of value in capitalist society, as there it has no "empirical reality"; 2) that if the philosophical dimension of Smithian political economy is developed, the “early and rude society” can be understood as a theoretical fiction that collaborates in the Smithian attempt to forge a law of universal scope.